2012
DOI: 10.1371/journal.pone.0049530
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochia Manshuriensis Kom Inhibits Adipocyte Differentiation by Regulation of ERK1/2 and Akt Pathway

Abstract: Aristolochia manshuriensis Kom (AMK) is a traditional medicinal herb used for the treatment of arthritis, rheumatism, hepatitis, and anti-obesity. Because of nephrotoxicity and carcinogenicity of AMK, there are no pharmacological reports on anti-obesity potential of AMK. Here, we showed AMK has an inhibitory effect on adipocyte differentiation of 3T3-L1 cells along with significantly decrease in the lipid accumulation by downregulating several adipocyte-specific transcription factors including peroxisome proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…As shown in Figure 4(d), inhibitor of Erk phosphorylation (PD98059) treatment induced the significant inhibition of Erk phosphorylation, as a positive control for HRT treatment. Akt pathway has been shown to regulate adipocyte differentiation by modulation of PPAR- γ expression [14]. In this study, we found that HRT significantly decreased phosphorylation of Akt compared with control (Figure 5(a)).…”
Section: Resultssupporting
confidence: 53%
“…As shown in Figure 4(d), inhibitor of Erk phosphorylation (PD98059) treatment induced the significant inhibition of Erk phosphorylation, as a positive control for HRT treatment. Akt pathway has been shown to regulate adipocyte differentiation by modulation of PPAR- γ expression [14]. In this study, we found that HRT significantly decreased phosphorylation of Akt compared with control (Figure 5(a)).…”
Section: Resultssupporting
confidence: 53%
“…Medicinal plants and their extracts have been verified as beneficial and are the oldest and most widespread form of medication to prevent diet-induced obesity [12,13,14]. Multiple natural products containing numerous bioactive compounds may result in synergistic activity that increases their bioavailability and action on multiple molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…During adipogenesis of 3T3-L1 cells, peroxisome proliferator-activated receptor- γ (PPAR- γ ) and CCAAT/enhancer-binding protein- α (C/EBP- α ) play key roles as major transcription factors [5]. Expression of PPAR- γ , a transcription factor of the nuclear-receptor superfamily, and C/EBP- α , a member of the C/EBP family of basic-leucine zipper class of transcription factors, increased during differentiation of 3T3-L1 cells [6]. …”
Section: Introductionmentioning
confidence: 99%